2015
DOI: 10.15713/ins.jmrps.14
|View full text |Cite
|
Sign up to set email alerts
|

The size and morphology of sella turcica: A lateral cephalometric study

Abstract: Background: Sella turcica is a saddle-shaped concavity in the body of sphenoid bone situated in the middle cranial fossa of skull, clearly seen on lateral cephalometric radiograph. Aim: The purpose of the study was to measure the size and describe the morphology of sella turcica in different age groups and gender. Materials and Methods: Lateral cephalometric radiographs of 200 subjects of which 100 males and 100 females in the age group of 8-30 years were included in the study population. Linear dimensions whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 13 publications
(16 reference statements)
9
38
1
7
Order By: Relevance
“…Similarly, Preston [18] determined a close correlation between sella area and age. Nagaraj et al [16] described increasing sella depth and AP diameter with increasing age. Hasan et al [14] reported that sella turcica dimensions differed significantly between age groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Preston [18] determined a close correlation between sella area and age. Nagaraj et al [16] described increasing sella depth and AP diameter with increasing age. Hasan et al [14] reported that sella turcica dimensions differed significantly between age groups.…”
Section: Discussionmentioning
confidence: 98%
“…When Hasan et al [14] compared the dimensions of the sella turcica by gender and found no relevant differences between males and females, expect in sella height anterior. Ashraf et al, [1] Shah et al, [8] Najim and Al-Nakib, [13] Olubunmi et al [15] and Nagaraj et al [16] reported that sella morphometry did not differ between males and females. Silverman [17] found differences in the size of sella between genders in the preadulthood period, but no difference between males and Table 2 Comparison of sella turcica morphometry according to the decades.…”
Section: Discussionmentioning
confidence: 99%
“…There was difference in the linear measurements of depth, and anteroposterior diameter in each age group which increased as age increased and the difference was statistically significant with P < 0.05. Choi et al also reported that lin-ear dimensions of sella turcica had positive inclination with the age 24) . Based on the results of this study, gender differences were statistically insignificant for all linear and area measurements of sella turcica.…”
Section: Shape Of the Sella Turcicamentioning
confidence: 91%
“…Более широкое распространение при проведении иденти-фикации личности находят рентгенологические исследо-вания, так как неуклонно растет появление новых, более совершенных методов лучевой и компьютерной диагно-стики [3,4,6,[27][28][29][30][31]. А.В.…”
Section: современные методы идентификацииunclassified